Clinical study and management of surgical problem of hepatobiliary and pancreatic disease in children - Khasnis, Ravindra G.; S., Rajshankar (International Surgery Journal, 2019)
Background: Conditions which can be treated by surgery like biliary atresia etc., can lead to infantile jaundice. For better outcome it is important that the diagnosis be made quickly and precisely. There is danger of irreversible damage to the liver if prompt action is not taken. Here comes the role of diagnostic imaging which can help for prompt and precise diagnosis. This helps to act rapidly for the surgeon. The objective was to study the surgical problem of hepatobiliary and pancreatic disease in children. Methods: Hospital-based follow up study was carried out among 10 pediatric patients with surgical problems hepatobiliary and pancreatic diseases. After admission detailed history of all the cases were taken according to the proforma approved by the guide information regarding the age at presentation to hospital, gestational age, birth weight, age at onset of jaundice, nature of symptoms, duration of symptoms was obtained. Results: Out of the total cases, 50% constituted the biliary atresia cases followed by choledochal cyst in 30% of the cases. Chronic pancreatitis constituted 20% of the cases. In 20% of the patients the birth weight was less than two kg. All 5 patients had icterus. 3 patients had icterus. Ultrasound showed that the most common finding was hepatomegaly in 60% of the cases. All 5 patients had good uptake of radiotracer and excretion of radiotracer in intestine was poor in all 5 patients. The mean value of total bilirubin is 13.9. Conclusions: Early and rapid intervention in biliary atresia cases reduces morbidity and mortality.